MCC950, a Selective Inhibitor of NLRP3 Inflammasome, Reduces the Inflammatory Response and Improves Neurological Outcomes in Mice Model of Spinal Cord Injury - Jiao, Jianhang; Zhao, Guanjie; Wang, Yang; Ren, Pengfei; Wu, Minfei (Frontiers in Molecular Biosciences, 2020)
Spinal cord injury (SCI) is a serious condition that affects bodily function; however, there is no effective therapy in clinical practice. MCC950, a selective NOD-like receptor protein-3 (NLRP3) inflammasome inhibitor, has been reported to alleviate canonical and noncanonical NLRP3 inflammasome activation of the inflammatory response in vitro and in vivo. However, the effect of MCC950 treatment on neurological post-SCI recovery remains unclear. In this study, we assessed the pharmacological effect of MCC950 on an experimental SCI model in vivo and neuronal injury in vitro. We found that MCC950 improved the grip strength, hind limb movements, spinal cord edema, and pathological injury in the SCI mice. We demonstrated that it exerted this effect by blocking NLRP3 inflammasome assembly, including NLRP3-ASC and NLRP3-Caspase-1 complexes, as well as the release of pro-inflammatory cytokines TNF-α, IL-1β, and IL-18. Moreover, we found that MCC950 reduced spinal neuron injury and NLRP3 inflammasome activation, which had been induced by oxygen-glucose deprivation or lipopolysaccharides in vitro. In conclusion, our findings indicate that MCC950 alleviates inflammatory response and improves functional recovery in the acute mice model of SCI by blocking NLRP3 inflammasome assembly and alleviating downstream neuroinflammation. Therefore, these findings could prove useful in the development of effective therapeutic strategies for the treatment and prognosis of SCI.